ETIKA LINGKUNGAN DALAM PERSPEKTIF TEORI KESATUAN WUJUD TEOSOFI TRANSENDEN - Muhammad Yasser (Sekolah Tinggi Agama Islam Sadra, 2014)
The study of environmental ethics based on the theory of oneness of being of Transcendent Theosophy has frontally criticizes modern scientific paradigm which is anthropocentric in character. This particular perspective believes that only man who posses value in itself (intrinsic value), while other being posses only instrumental value in relation to man interests. On the other hand, it also criticizes the ecocentric perspective which considers nature to posses her own value independently from man. The principle of oneness of being (wahdat al-wujūd) is the main (ontological) argumentation used by muslim philosophers, including Mulla Sadra as the founder of Transcendent Theosophy, in answering all cosmological questions and concerns throughout the ages. The Transcendent Theosophy itself is a (relatively) new perspective in the tradition of Islamic philosophy, which is based on a creative synthesis and harmonization of nearly all the earlier schools.